BUM Desa sebagai Tonggak Ekonomi Desa - Putera Perdana (Jurnal Masyarakat dan Desa, 2025)
This study aims to determine the extent to which BUM Desa is able to become a village economic milestone, after the issuance of the Village Law many villages are competing to establish BUM Desa, some of which were born from community initiatives, some were established due to Regional Government intervention. The purpose of BUM Desa is to strengthen the economy of the community and increase the village's original income. BUM Desa is also known as a Hybrid Institution because BUM Desa is a form of collaboration between the Village Government and its citizens to utilise shared resources owned by the village for the welfare of the citizens. The method used in this research is qualitative with a case study approach to obtain in-depth data. The research results from 3 locations, namely Panggungharjo Village, Melikan Village and Bleberan Village, show that the seriousness in planning and reading the existing potential at the local level as well as the idea of presenting BUM Desa are the determining factors for the success of BUM Desa as a village economic milestone. It can be concluded that the success of BUM Desa is also determined by the type of business to be conducted and in accordance with the local potential in the village as well as the working system of BUM Desa management